Effectiveness Treatment for Diabetes Prevention: 6-Months Results from the Prediabetes - Mubeen, Dr. Mohd Faheem; Bhosle, Dr. Deepak (International Journal of Innovative Research in Medical Science, 2019)
ADA has the same cut-off value for IGT (140-200 mg/dL) but has a lower cut-off value for IFG (100-125 mg/dL) and has additional hemoglobin A1c (HbA1c) based criteria of a level of 5.7% to 6.4% for the definition of prediabetes. Due to progressive nature of prediabetes to diabetes, dual drug therapy produces additive effects, allows the use of submaximal doses, and less side effects of individual agents. Therefore, the present study was designed to study the effect of FDC of Metformin with Pioglitazone Versus FDC of Metformin with Voglibose on Lipid levels as an add-on drug in obese with prediabetes patients whose dyslipidemia status was uncontrolled with metformin alone. Material and Methods: The present study was open, randomized parallel group comparison of two active treatment groups over a period of six months. Sixty-seven patients of either sex in the age group of 30-60 years, suffering from obese with prediabetes, with FBG: 100-125 mg/dl and PPBG: 140-200 mg/dl as per ADA were selected at randomly. The effect of FDC of Metformin with Pioglitazone and FDC of Metformin with Voglibose were observed on various parameters of FBG, PPBG, Serum Adiponectin and Serum ghrelin levels. Results: At the end of 3rd and 6th months it was observed that though both FDC of Metformin with Pioglitazone and FDC of Metformin with Voglibose reduced Blood Glucose significantly but FDC of Metformin with Pioglitazone caused a statistically significantly greater amount change in FBG, Serum Adiponectin and Serum ghrelin levels as compared with FDC of Metformin with Voglibose. Conclusions: Though FDC of Metformin with Pioglitazone and Metformin with Voglibose were equally effective in lowering FBG, Serum Adiponectin and Serum ghrelin levels yet Metformin with Pioglitazone showed better results in improving Glycemia, as compared with FDC of Metformin with Voglibose.